(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The issue of "paradigm" is always interesting to be discussed and debated. Differing views of jurists preceded by a paradigm that is used in building the argument juridical (legal reasoning). That difference, also under the influence of methods of learning in higher education law. This implies, that a scientist law will never probably be in the zero point in issuing his views and will always be subjective. The issue becomes interesting, when Indonesia, was clearly an explicit through the fourth paragraph of the preamble NRI 1945 confirms Pancasila as a paradigm of the whole life of the state and society. Thus, Pancasila is the only paradigm (Philosophy) Law recognized and acknowledged in some legislation. So, again the problem is whether the law enforcement in Indonesia has been able to absorb the essence of Pancasila it self.